Pre-eclampsia and the risk of attention-deficit/hyperactivity disorder in offspring: Findings from the ALSPAC birth cohort study - Dachew, B.; Scott, J.; Mamun, A.; Alati, Rosa (Elsevier Ireland Ltd, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is a prevalent heterogeneous neurodevelopmental syndrome associated with various environmental factors. This study examined the association between maternal pre-eclampsia and offspring ADHD at 7- and 10-years. The study cohort consisted of more than 7200 children who participated in Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort study. ADHD was diagnosed using parent reported Development and Wellbeing Assessment (DAWBA). Log-binomial regression and Generalized Estimating Equation (GEE) models were used. The GEE analysis showed that pre-eclampsia was associated with increased risk of ADHD in offspring (adjusted risk ratio [RR] = 2.77; 95% confidence interval [CI] = 1.42–5.38). Similarly, the results of multivariable log-binomial regression analysis at each time point showed that pre-eclampsia was associated with an almost threefold increase risk of offspring ADHD. This study suggests that offspring of mothers with pre-eclampsia are at increased risk of ADHD, although residual and unmeasured confounding by environmental and genetic factors warrants further study. If our findings are replicated by others, early screening for ADHD and other developmental delays may be recommended in offspring of women with pre-eclampsia.